The relationship between abdominal obesity and irritable bowel syndrome in adults - UZUNER, ARZU (My University, 2022)
ABSTRACTObjective: The aim of this study is to evaluate the relationship between irritable bowel syndrome (IBS) and abdominal obesity.Patients and Methods: This is a cross-sectional study, consisting of 18-49 year old patients who applied to Marmara University Schoolof Medicine’s Family Medicine outpatient clinics and who accepted to participate. A questionnaire was applied using face-to-faceinterview technique; anthropometric measurements were obtained as recommended by World Health Organization (WHO). Thediagnosis of IBS was made for those who fully met the diagnostic criteria of ROME IV-IBS and had no alarm symptoms. Abdominalobesity of the participants was determined via anthropometric measurements. Statistical analyses were performed by using SPSS 20package program.Results: A total of 487 patients participated in the study: 77% female, 33% male; mean age value 33.71±8.59 years. The prevalenceof IBS was 24.2% (n=118) [F:27.2% (n=102), M:14.3% (n=16)]. Abdominal obesity prevalence was 31.2% (n=152) [F:24.5% (n=92,M:53.6% (n=60)]. There is no statistically significant difference in terms of abdominal obesity with and without IBS (p>0.05).Conclusion: In this study no statistically significant relationship has been detected between IBS and abdominal obesity.Keywords: Irritable bowel syndrome, Abdominal obesity, Central obesity
Keywords: Tıp; Dahili Tıp Bilimleri; Aile Hekimliği; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Family Medicine; Health Sciences; Klinik Tıp (MED); Klinik Tıp; SAĞLIK BAKIM BİLİMLERİ VE HİZMETLERİ; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; HEALTH CARE SCIENCES & SERVICES; MEDICINE, GENERAL & INTERNAL; Tıbbi Terminoloji; Tıbbi Sekreterlik ve Transkripsiyon; Sağlık Bilgi Yönetimi; Sağlık Meslekleri (çeşitli); Genel Sağlık Meslekleri; Gözden Geçirme ve Sınav Hazırlığı; Patofizyoloji; Liderlik ve Yönetim; Temel Bilgi ve Beceriler; Toplum Sağlığı ve Evde Bakım; Bakım Planlaması; Değerlendirme ve Teşhis; Dahiliye; Sağlık Politikaları; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; Medical Terminology; Medical Assisting and Transcription; Health Information Management; Health Professions (miscellaneous); General Health Professions; Review and Exam Preparation; Pathophysiology; Leadership and Management; Fundamentals and Skills; Community and Home Care; Care Planning; Assessment and Diagnosis; Internal Medicine; Health Policy; Family Practice; Medicine (miscellaneous); General Medicine